Diagnostic Accuracy of Magnetic Resonance Cholangiopancreatography in Comparison to Endoscopic Retrograde Cholangiopancreatography in Obstructive Biliopathy - Muhammad Ayub Naich, Sagheer Hussain, Hina Zamir, Adeel Qamar, Fatima Cheema, Zia Ul Mustafa, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the diagnostic accuracy of magnetic-resonance-cholangio-pancreatography (MRCP) in diagnosis of obstructive biliopathy in comparison to endoscopic retrograde cholangio-pancreatography (ERCP) taking as gold standard. Study design: It is a cross sectional study. Place and duration of study: Study was conducted on the patients admitted in the gastroenterology department of Sir Ganga Ram Hospital Lahore. Study was completed in six months duration from January 2022 to June 2022. Methodology: Patients with the suspicion of obstructive biliopathies requiring ERCP were included in this study. Study sample was divided into two groups, in one group ERCP was done while other group underwent MRCP. Resulst of both techniques were reviewed by radiologist and gastroenterologist and compared with each other considering ERCP as gold standard. P-value <0.05 was considered statistically significance. Confidence interval was 95%. Results: Total 130 cases were divided into two groups with equal number of 65 patients in each. There were 75(57.6%) female and 55(42.3%) male cases. Mean age of the patients was 43.7± 3.5 years. Sensitivity of MRCP for obstructive biliopathies was 92.4%, specificity 90.7%, positive predictive value 88.3% and negative predictive value 89.2%. Conclusion: MRCP is a non-invasive investigation of choice in obstructive biliopathies having high diagnostic accuracy avoiding unnecessary complications of ERCPs. Keywords: MRCP, ERCP, Obstructive Biliopathy, CBD Stone, Stricture